STUDENTS’ READING COMPREHENSION IN LEGEND BY USING MAKE A MATCH - Khairunnisah Khairunnisah (STBA Pontianak, 2022)
The aims of the research were to find out the students’ reading comprehension in legend before using Make a Match Strategy, beside, to know the students’ difficulties in improvement reading comprehension by using Make a Match Strategy, and also to find out the students’ improvement by using Make a Match Strategy in reading comprehension at the grade VIII of SMP Negeri 1 Panyabungan. The writer applying this research with Classroom Action Research (CAR) used e-class was using Whats App. The subject of research was the grade VIII-1 students of SMP Negeri 1 Panyabungan. They were 30 students. The resulted shown students’ reading comprehension improves significantly, it shown from the resulted students’ percentage of pretest was 13,33%, cycle I was 53,33 %, and in cycle II was 90%. Make a Match Strategy can help students to improve reading Comprehension.